Increased isolation of two biosphere reserves and surrounding protected areas (WAP ecological complex, West Africa) (2007)
Protected areas such as nature reserves have been found to be effective in preventing habitat destruction and protecting ecosystems within their borders. Recent studies however found extensive loss of tropical forest habitat around protected areas, vastly contributing to increase the levels of ecological isolation. Using high-resolution satellite data we investigated the isolation trend occurring in the W-Arly-Pendjari (WAP) ecological complex in West Africa. A land-cover change analysis was performed for the period 1984–2002: savanna vegetation extension and loss were derived within the complex and in a 30 km peripheral buffer. Sample regions in the buffer were also analysed using selected spatial indicators to quantify temporal trends in habitat fragmentation. Implications for change in relative capacity to conserve biodiversity were discussed through the calculation of the species richness capacity (SRC). More than 14.5% of savanna habitat was lost in the WAP peripheral areas, while 0.3% was converted inside the complex. The degree of fragmentation of remnant savanna habitat has also drastically increased. Despite the effectiveness of the park conservation programme, we found through the SRC approach that the WAP complex is decreasing its potential capacity to conserve species richness. This process is mainly due to the rapid and extended agricultural expansion taking place around the complex. A better understanding of the ecological dynamics occurring in the peripheral regions of reserves and the consideration of development needs are key variables to achieve conservation goals in protected areas.